Clinical and dosimetric evaluation of recurrent breast cancer patients treated with hyperthermia and radiation. (1st January 2019) - Dharmaiah, Sharvari; Zeng, Johnathan; Rao, Vinay S.; Ouyang, Zi; Ma, Tianjun; Yu, Kevin; Bhatt, Heeruk; Shah, Chirag; Godley, Andrew; Xia, Ping; Yu, Jennifer S.
Abstract: Background: Treatment for locally recurrent breast cancer poses a significant challenge because the benefits in local control must be weighed against the increased risk of side effects of the treatment. Frequently, patients have been heavily pre-treated with radiation and several types of chemotherapy. Moreover, they often present with large volumes of bulky disease, further complicating management. Hyperthermia can be used to improve the efficacy of radiation, particularly in the setting of recurrent disease. Methods: We reviewed our clinical and dosimetric experience of breast cancer patients who received hyperthermia and radiation for recurrent breast cancer from 2011 to 2017. Thirty-six patients were treated with hyperthermia and radiation. Median follow-up was 11 months. Thirty patients (83.3%) received prior radiotherapy. The most commonly used radiation fraction scheme was 32 Gy in 8 fractions. The median radiation dose at the time of recurrence was 35.5 Gy (range 20–64 Gy). Mild temperature hyperthermia was delivered two times per week. Results: The median repeat radiation volume was 574 cc (range 11–3620 cc). Electrons, conventional photons, and IMRT radiation techniques were used. IMRT was used for large and complex treatment volumes and showed acceptable doses to organs at risk. The overall response rate was 61.1%. Complete response was observed in 17 patients (47.2%), partial response in 5 patients (13.9%), stable disease in 11 patients (30.6%), and progressive disease in 3 patients (8.3%). Twenty-six patients experienced acute grade 1 and 2 toxicities, primarily pain and erythema; and 26 experienced long-term grade 1 and 2 toxicities, mainly hyperpigmentation and lymphedema. Three patients developed new ulcerations that healed with conservative management. One patient developed pulmonary fibrosis resulting in mild dyspnea on exertion. Conclusion: Hyperthermia and radiation provide good local control with a favorable side effect profile. Thermoradiotherapy may be offered to patients with recurrent breast cancer, including those with extensive volumes of disease.